Gestión de seguridad y salud en el trabajo en la prevención de riesgos laborales en la manipulación de postes en electrificación rural de la Provincia de Chota, Departamento de Cajamarca, 2019 - Eguizabal Sifuentes, Adderly Armando (2022)
An efficiently implemented Occupational Health and Safety Management System (SG-SST) fosters the creation of safe and healthy work environments. Hence the importance of the study that will support both the workers and mainly the companies to prioritize the development and implementation of safe procedures, and their monitoring and control regarding the work they perform. The present investigation was carried out in the execution of a work by contract for the integral electrification of the province of Cutervo, Cajamarca in the year of 2019, by the Virgen del Prado Consortium, with the objective of evaluating the safe work procedures according to the SG-SST for the prevention of occupational risks in rural electrification. It is an observational, analytical, cross-sectional investigation. The list of SG-SST MTPE guidelines, criteria and evaluation scores were used to determine the level of implementation of the SG-SST in the Virgen del Prado Consortium. Finally, it is concluded; that the best levels of implementation of the SGSST in the Virgen del Prado Consortium is achieved in the guideline, Evaluation of compliance with regulations with 75 percent, followed by the guideline of Occupational health and safety policies with 61.36 percent. But, at a general level, the Virgen del Prado Consortium has not been adequately complying with all the SG-SST guidelines, obtaining a score of 236, which represents an overall result of 51.75 percent. With this percentage of compliance with the SGSST, the Virgen del Prado Consortium reaches a REGULAR level of compliance with the guidelines of its respective SG-SST at Work in comprehensive electrification activities.